THE IMPACT OF WATCHING COCOMELON ON THE VERBAL AND ORAL DEVELOPMENT OF TODDLERS - Cindy Shinta Ayu; Munawwir Hadiwijaya (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
This study examines the impact of watching CocoMelon on the verbal and oral development of toddlers. CocoMelon, a popular YouTube channel featuring songs and interactive stories for children, has become an integral part of daily life for many families worldwide. This study uses a qualitative method with a case study approach, involving in-depth interviews with parents and direct observation of toddlers who regularly watch CocoMelon. The results show that watching CocoMelon can have a positive impact on children's verbal and oral development by introducing new vocabulary and encouraging their interest in speaking and singing. However, excessive use without proper supervision can negatively affect children's language development. This study highlights the importance of parental involvement in monitoring and limiting screen time to ensure that educational content like CocoMelon is effectively used to support language development in children.